Molecular and Clinical Perspectives on Cytokine Storms and Seasonal Influenza Infections - Wurood Kadhim Abed; Thualfakar Hayder Hasan Abed; Maha Mashrq AlBayati (Journal of Biomedicine and Biochemistry, 2025)
Background: Seasonal influenza may cause severe complications in case of cytokine storm, a hyperinflammatory reaction that increases tissue damage and dysfunction of multiple organs. Objective: The research aims were to determine the correlation between seasonal influenza and cytokine storm through clinical and molecular investigations. Methods: A cross-sectional observational study was carried out on 120 patients with RT-PCR-confirmed seasonal influenza in December 2023-March 2024. ELISA was used to determine serum levels of IL-6, TNF-α, IFN- g, IL-1, and IL-18. Demographics and clinical information, such as ARDS, coagulopathy, acute kidney injury, CNS manifestations, etc., were documented. Statistical significance of p = 0.05 was used to test statistical significance with SPSS v26.0 (t-test, Mann- Whitney, Pearson/Spearman correlation). Results: The patients with cytokine storm (n = XX) had much more serum cytokines than their uncomplicated influenza counterparts (IL-6: 142 ± 35 vs. 18 ± 6 pg/mL, p < 0.001; TNF-α a: 96 ± 22 vs. 15 ± 5 pg/mL, p < 0.001). The incidence of coagulopathy (70% vs. 5%), AKI (40% vs. 5%), and CNS (confusion 45% vs. 10%) was significantly higher. High IL-6 levels were greatly associated with ARDS (r = 0.68, p < 0.01). Conclusion: In seasonal influenza, cytokine storm is related to hyper-release of IL-6, TNF-α, IFN- gamma, IL- 1 8, and IL-1α, which cause dysfunction of multiple organs and increased complications. The timely identification of the signs of cytokine storm would enhance the outcome of patients and inform the use of specific immunomodulatory treatment.